A magnetic titanium-based lithium adsorbent and preparation method thereof
By adopting magnetic titanium lithium adsorbent, the material combines a strong magnetic magnetic core and a titanium oxide coating, solving the problem of difficulty in applying it to strong alkaline and carbonate brines in the prior art, achieving efficient lithium adsorption and stability, extending service life, and supporting effective recycling.
Patent Information
- Application Number
- CN202111567446.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-12-20
AI Technical Summary
The existing magnetic aluminum-based lithium adsorbents and magnetic lithium manganese spinels are difficult to be used in highly alkaline and carbonate-type brines to extract lithium, and their binding force with the magnetic core is insufficient, resulting in difficult recovery of lithium adsorbents.
A magnetic titanium lithium adsorbent is used, which includes a magnetic composite and a lithium adsorption layer. The magnetic composite consists of a strong magnetic core and a titanium oxide cladding layer, and the lithium adsorption layer is composed of lithium titanium oxide. The material is prepared by calcination and pre-desorption treatment to ensure the close bond between the lithium adsorption layer and the magnetic composite.
This magnetic titanium lithium adsorbent can efficiently adsorb lithium in strong alkaline and carbonate type brines, and has high stability under strong alkaline conditions, extends service life, and can be effectively recovered, expanding the scope of application of lithium extraction in brines.
Smart Images

Figure BDA0003422232080000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic lithium adsorbent materials, and specifically relates to a magnetic titanium-based lithium adsorbent and a preparation method thereof. Background Art
[0002] With the rapid development of electric bicycles, electric vehicles and the electronics industry, lithium batteries and lithium power batteries have become indispensable products, and the global demand for lithium resources is increasing. Salt lake brine, seawater, etc. contain rich liquid lithium resources, which are the main resources for the lithium industry in the future. How to extract lithium from these liquid ores has become an important topic. At present, adsorption of lithium is regarded as the most promising way to extract lithium. In recent years, lithium adsorbents have gradually been widely studied by scholars as a new type of material. Because lithium ions are embedded in this lithium adsorbent, it has a certain memory function for lithium ions and has a stable adsorption capacity and elution rate. In order to facilitate the recovery of lithium adsorbents, magnetic materials are usually introduced into lithium adsorbents.
[0003] There is a magnetic aluminum-based lithium adsorbent, the preparation method of which is: adding ferroferric oxide powder to deionized water, adding a dispersant, assisting with ultrasound and strong stirring, adding AlCl 3 Powder, disperse and stir to make AlCl 3 After that, sodium hydroxide powder is added into the system to make aluminum hydroxide gradually deposit on the interface of ferroferric oxide to obtain magnetic core @Al(OH) 3 ·nH 2 O. Then, LiCl powder was added to the above system, and the magnetic core @LiX·2Al(OH) was obtained after dispersion and reaction. 3 ·nH 2 O. The mixed solution is separated into solid and liquid by a magnetic separator, filter press or centrifuge to obtain the dehydrated magnetic core @LiX·2Al(OH) 3 ·nH 2 O, becoming a magnetic aluminum-based lithium adsorbent.
[0004] There is another magnetic lithium manganese spinel, the preparation method of which is as follows: adding a mixed solution of ethanol and water to ferroferric oxide powder, adding ethyl orthosilicate under stirring conditions, and then stirring for a certain period of time, pumping the mixed solution into an electromagnetic separator again to magnetically separate the ferroferric oxide magnetic cores coated with silicon dioxide, pumping the ferroferric oxide magnetic cores coated with silicon dioxide into a manganese chloride solution under stirring conditions, and adding a lithium hydroxide solution, stirring and then standing for aging to obtain a magnetic lithium manganese compound, drying at 60°C, and then placing in a kiln and calcining at 350°C for 5 hours to obtain the magnetic lithium manganese spinel.
[0005] Existing magnetic aluminum-based lithium adsorbents and magnetic lithium manganese spinels are not suitable for adsorbing lithium in strongly alkaline and carbonate-type brines. Among them, magnetic aluminum-based lithium adsorbents will react with carbonate to form precipitation, and are only suitable for adsorbing lithium in chloride-type brines; and magnetic lithium manganese spinels are prone to Mn dissolution under weak acid and strong alkaline conditions, resulting in decreased adsorption performance, and are only suitable for adsorbing lithium in neutral to weakly alkaline brines. On the other hand, the existing lithium adsorbents are not tightly bound to the magnetic core and are prone to falling off. After multiple uses, the lithium adsorbents are difficult to recover due to the mutual separation of the outer layer of the adsorbent and the magnetic core. Summary of the invention
[0006] In view of the problem that existing magnetic lithium adsorbents are difficult to be used for lithium extraction in strongly alkaline and carbonate-type brines, the present invention provides a magnetic titanium-based lithium adsorbent and a preparation method thereof.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0008] On the one hand, the present invention provides a magnetic titanium-based lithium adsorbent, comprising a magnetic composite and a lithium adsorption layer, wherein the lithium adsorption layer is located on the outer surface of the magnetic composite, the magnetic composite comprises a magnetic material and titanium oxide, and the lithium adsorption layer comprises lithium titanium oxide.
[0009] Optionally, the magnetic composite includes a ferromagnetic core and a titanium oxide coating layer, the ferromagnetic core contains one or more of ferroferric oxide, iron, cobalt, nickel and ferrite, and the titanium oxide coating layer is coated on the outer surface of the ferromagnetic core.
[0010] Optionally, the ferromagnetic core is selected from ferrosoferric oxide, and the titanium oxide coating layer is selected from TiO 2 , the TiO 2 The molar ratio of the Ti element in the ferroferric oxide to the Fe element in the ferroferric oxide is 1:2 to 1:5.
[0011] Optionally, the average particle size of the magnetic composite is 20-120 nm, the average particle size of the ferromagnetic core is 10-100 nm, the thickness of the titanium oxide coating layer is 5-20 nm, and the thickness of the lithium adsorption layer is 5-50 nm.
[0012] Optionally, the saturation magnetization intensity of the magnetic composite is 20 to 60 emu / g.
[0013] Optionally, the lithium adsorption layer is a porous structure, and the pore volume of the lithium adsorption layer is 0.01 ml / g to 0.30 ml / g.
[0014] Optionally, the lithium titanium oxide is selected from Li 4-x Ti 5-y My O 12 , wherein x is selected from 0 to 2, y is selected from 0 to 0.1, and M is one or more of Mg, Cr, Co, Ni, Mo, Zr, and Zn.
[0015] Optionally, the magnetic titanium-based lithium adsorbent also includes an outer coating layer, which is located on the outer surface of the lithium adsorption layer. The outer coating layer is a metal oxide, wherein the metal oxide is one or more oxides of Mg, Cr, Co, Ni, Mo, Zr, Ti, Zn, and Li, and the thickness of the outer coating layer is 1 to 10 nm.
[0016] On the other hand, the present invention provides a method for preparing a magnetic titanium-based lithium adsorbent, comprising the following steps:
[0017] Obtaining a magnetic composite: the magnetic composite comprises a magnetic material and titanium oxide;
[0018] Preparation of a magnetic titanium-based lithium adsorbent precursor: adding the magnetic composite to a titanium salt solution and a lithium salt solution for reaction, and separating to obtain intermediate product particles; calcining the intermediate product particles to form a lithium adsorption layer on the outer surface of the magnetic composite to obtain a magnetic titanium-based lithium adsorbent precursor;
[0019] Pre-desorption: The magnetic titanium-based lithium adsorbent precursor is placed in an acidic solution for pre-desorption treatment to remove part of the lithium in the lithium adsorption layer to obtain the magnetic titanium-based lithium adsorbent.
[0020] Optionally, the method for preparing the magnetic composite comprises the following steps:
[0021] Preparing an iron salt solution: the iron salt solution includes divalent iron ions and trivalent iron ions;
[0022] Fe 3 O 4 Dispersion preparation: Add ammonia water to the iron salt solution at a temperature of 40-60°C to separate Fe 3 O 4 Dispersion;
[0023] Coating: Nano-TiO 2 Configured TiO 2 Dispersion solution, mixed Fe 3 O 4 Dispersions and TiO 2 The dispersion is separated into a solid and liquid state to obtain a magnetic composite.
[0024] Optionally, in the iron salt solution, the iron ion concentration is 0.5-3 mol / L, wherein the molar ratio of divalent iron ions to trivalent iron ions is 1:2; 2The weight of the dispersion solution is 100%, TiO 2 The added mass is 10wt.%~20wt.%.
[0025] Optionally, after obtaining the magnetic composite, the magnetic composite is washed with deionized water and anhydrous ethanol, dried and then ground. After grinding, the particle size of the magnetic composite is 20 to 120 nm.
[0026] Optionally, in the operation of "preparing a magnetic titanium-based lithium adsorbent precursor", the magnetic composite is added to a stirred titanium salt solution, and then a lithium salt solution is added for reaction, and the molar ratio of the Fe element in the magnetic composite to the Li element in the lithium salt solution is controlled to be 1:5 to 1:10, and the molar ratio of the Li element in the lithium salt solution to the Ti element in the titanium salt solution is controlled to be 0.5:1 to 1:3.
[0027] Optionally, in the operation of "preparing a magnetic titanium-based lithium adsorbent precursor", the titanium salt solution includes a solution of one or more of titanyl sulfate or titanic acid, and the concentration of the titanium salt solution is 1 to 4 mol / L; the lithium salt solution includes a solution of one or more of lithium chloride, lithium sulfate, lithium hydroxide, lithium nitrate and lithium acetate, and the concentration of the lithium salt solution is 1 to 3 mol / L.
[0028] Optionally, before calcination, a metal salt is added to the intermediate product particles for doping.
[0029] Optionally, after calcination, metal oxide is added to the magnetic titanium-based lithium adsorbent precursor and calcined and coated again.
[0030] The magnetic titanium lithium adsorbent provided by the present invention comprises a magnetic composite and a lithium adsorption layer, wherein the lithium titanium oxide in the lithium adsorption layer acts as a lithium adsorbent, and is characterized in that it can adsorb lithium in strongly alkaline and carbonate-type brines, does not react with carbonate in brine, and has high stability under strongly alkaline conditions, effectively expanding the scope of application of lithium extraction in brine. The magnetic composite contains titanium oxide and magnetic material, and the magnetic material is used to provide the magnetic properties of the magnetic composite, so that the magnetic titanium lithium adsorbent that adsorbs lithium can be magnetically separated and recovered when the magnetic titanium lithium adsorbent is used to perform lithium enrichment operations on brine. The titanium oxide can participate in the synthesis of lithium titanium oxide in the lithium adsorption layer, so that the magnetic composite and the lithium adsorption layer are more closely combined, effectively preventing the lithium adsorption layer from falling off the surface of the magnetic composite during the long-term use of the magnetic titanium lithium adsorbent, and extending the service life of the magnetic titanium lithium adsorbent. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] An embodiment of the present invention provides a magnetic titanium-based lithium adsorbent, comprising a magnetic composite and a lithium adsorption layer, wherein the lithium adsorption layer is located on the outer surface of the magnetic composite, the magnetic composite comprises a magnetic material and titanium oxide, and the lithium adsorption layer comprises lithium titanium oxide.
[0033] The magnetic titanium lithium adsorbent includes a magnetic composite and a lithium adsorption layer, wherein the lithium titanium oxide in the lithium adsorption layer plays the role of a lithium adsorbent, and is characterized in that it can adsorb lithium in strongly alkaline and carbonate-type brines, does not react with carbonate in brine, and has high stability under strongly alkaline conditions, effectively expanding the scope of application of lithium extraction in brine. The magnetic composite contains titanium oxide and magnetic material, and the magnetic material is used to provide the magnetic properties of the magnetic composite, so that the magnetic titanium lithium adsorbent that adsorbs lithium can be magnetically separated and recovered when the magnetic titanium lithium adsorbent is used to perform lithium enrichment operations on brine. Titanium oxide can participate in the synthesis of lithium titanium oxide in the lithium adsorption layer, so that the magnetic composite and the lithium adsorption layer are more closely combined, effectively preventing the lithium adsorption layer from falling off the surface of the magnetic composite during the long-term use of the magnetic titanium lithium adsorbent, and extending the service life of the magnetic titanium lithium adsorbent.
[0034] In different embodiments, the lithium adsorption layer is located on the entire outer surface or a portion of the outer surface of the magnetic composite.
[0035] In different embodiments, the magnetic material and titanium oxide in the magnetic composite can be combined in different forms. For example, the magnetic material and titanium oxide can be doped and mixed with each other, or titanium oxide can be used as a coating layer of the magnetic material.
[0036] In a preferred embodiment, the magnetic composite comprises a ferromagnetic core and a titanium oxide coating layer, wherein the ferromagnetic core comprises one or more of ferroferric oxide, iron, cobalt, nickel and ferrite, and the titanium oxide coating layer is coated on the outer surface of the ferromagnetic core.
[0037] By using titanium oxide as a coating layer for the ferromagnetic core, on the one hand, titanium oxide has good chemical inertness and can effectively provide a protective isolation effect for the ferromagnetic core inside it, thereby ensuring the stability of the ferromagnetic core and avoiding magnetic failure; on the other hand, it also increases the contact area between the magnetic composite and the lithium adsorption layer. Since the titanium oxide coating layer has good affinity with the lithium titanium oxide of the lithium adsorption layer, it is beneficial to improve the bonding strength between the magnetic composite and the lithium adsorption layer.
[0038] In a preferred embodiment, the magnetic material is selected from ferroferric oxide, and the titanium oxide coating layer is selected from TiO 2 , the TiO 2 The molar ratio of the Ti element in the ferroferric oxide to the Fe element in the ferroferric oxide is 1:2 to 1:5.
[0039] Ferroferric oxide has strong magnetism and good stability, and the material cost is low. It can show high magnetism, which is beneficial to the magnetic separation operation of the magnetic titanium-based lithium adsorbent.
[0040] In other embodiments, the titanium oxide coating layer may also be selected from titanium pentoxide.
[0041] Under the above-mentioned element ratio conditions, it can be ensured that the magnetic composite has sufficient Fe 3 O 4 To ensure the magnetization strength requirements, and also to make TiO 2 Can effectively coat Fe 3 O 4 The surface of the lithium ion battery provides a site for the formation of lithium titanium oxide in the subsequent lithium adsorption layer.
[0042] In some embodiments, the average particle size of the magnetic composite is 20-120 nm, the average particle size of the ferromagnetic core is 10-100 nm, the thickness of the titanium oxide coating layer is 5-20 nm, and the thickness of the lithium adsorption layer is 5-50 nm.
[0043] Among them, when the thickness of the titanium oxide coating layer is within the above range, it can better improve the bonding strength of the lithium adsorption layer on the ferromagnetic core, avoid the lithium adsorption layer from falling off during recycling, and will not have too much impact on the magnetism of the ferromagnetic core, so that it can meet the magnetization intensity required for magnetic separation.
[0044] Since the lithium adsorption amount of the magnetic titanium-based lithium adsorbent is determined by the content of the lithium adsorption layer, when the thickness of the lithium adsorption layer is within the above range, a higher lithium adsorption amount per unit volume can be achieved.
[0045] In some embodiments, the saturation magnetization of the magnetic composite is 20 to 60 emu / g.
[0046] In some embodiments, the lithium adsorption layer is a porous structure, and the pore volume of the lithium adsorption layer is 0.01 ml / g to 0.30 ml / g. The pore volume of the lithium adsorption layer is measured by a BET specific surface area test method.
[0047] When the lithium adsorption layer is selected from a porous structure, the contact area between the lithium adsorption layer and the brine can be increased, thereby facilitating the adsorption of lithium ions in the brine on the lithium adsorption layer and increasing the lithium adsorption capacity of the magnetic titanium-based lithium adsorbent.
[0048] In some embodiments, the lithium titanium oxide is selected from Li 4-x Ti 5-y M y O 12 , wherein x is selected from 0 to 2, y is selected from 0 to 0.1, and M is one or more of Mg, Cr, Co, Ni, Mo, Zr, and Zn.
[0049] When x is 0, the lithium titanium oxide is in a full lithium state and needs to be pre-desorbed by an acidic solution to remove some of the lithium ions in the lithium titanium oxide to form vacancies, thereby making x greater than 0. At this time, when the lithium titanium oxide encounters lithium ions in brine, it can attract lithium ions to embed into the lithium titanium oxide to reach a full lithium state. The lithium titanium oxide in a full lithium state can remove lithium ions again to achieve lithium ion enrichment and reuse of the magnetic titanium-based lithium adsorbent.
[0050] Wherein, the metal element M can be embedded in the lattice of the lithium titanium oxide in the form of doping to improve the structural stability of the lithium titanium oxide and reduce the dissolution of titanium ions in the lithium titanium oxide during long-term brine immersion. When y is selected from 0, the lithium titanium oxide is not doped with the metal element M.
[0051] In other embodiments, the magnetic titanium-based lithium adsorbent also includes an outer coating layer, which is located on the outer surface of the lithium adsorption layer. The outer coating layer is a metal oxide, wherein the metal oxide is one or more oxides of Mg, Cr, Co, Ni, Mo, Zr, Ti, Zn, and Li, and the thickness of the outer coating layer is 1 to 10 nm.
[0052] By coating the outer layer of the lithium adsorption layer with a metal oxide as an outer coating layer, the lithium adsorption layer can be protected, thereby avoiding direct contact between the lithium adsorption layer and brine, and effectively ensuring the molecular structure stability of the lithium adsorption layer.
[0053] When the outer coating layer is within the above thickness range, it can provide effective protection for the lithium adsorption layer and reduce the dissolution of titanium ions. The outer coating layer of this thickness allows lithium ions to pass through, avoiding blocking of lithium ions and having a high lithium ion adsorption efficiency.
[0054] Another embodiment of the present invention provides a method for preparing the magnetic titanium-based lithium adsorbent as described above, comprising the following steps:
[0055] Obtaining a magnetic composite: the magnetic composite comprises a magnetic material and titanium oxide;
[0056] Preparation of a magnetic titanium-based lithium adsorbent precursor: adding the magnetic composite to a titanium salt solution and a lithium salt solution for reaction, and separating to obtain intermediate product particles; calcining the intermediate product particles to form a lithium adsorption layer on the outer surface of the magnetic composite to obtain a magnetic titanium-based lithium adsorbent precursor;
[0057] Pre-desorption: The magnetic titanium-based lithium adsorbent precursor is placed in an acidic solution for pre-desorption treatment to remove part of the lithium in the lithium adsorption layer to obtain the magnetic titanium-based lithium adsorbent.
[0058] The magnetic titanium-based lithium adsorbent prepared by the preparation method can adsorb lithium ions in strong alkaline and carbonate-type brines, and has good structural stability and a long service life.
[0059] In some embodiments, the method for preparing the magnetic composite comprises the following steps:
[0060] Preparing an iron salt solution: the iron salt solution includes divalent iron ions and trivalent iron ions;
[0061] Fe 3 O 4 Dispersion preparation: Add ammonia water to the iron salt solution at a temperature of 40-60°C to separate Fe 3 O 4 Dispersion;
[0062] Coating: Nano-TiO 2 Configured TiO 2 Dispersion, mixed Fe 3 O 4 Dispersions and TiO 2 The dispersion is separated into a solid and liquid state to obtain a magnetic composite.
[0063] The Fe prepared by the above method 3 O 4 In the dispersion, Fe 3 O 4 With a larger particle size, Fe 3 O 4 The nucleus, while TiO 2 TiO in dispersion solution 2 The particle size is small, Fe 3 O 4 Dispersion and TiO 2 Dispersion mixing, TiO 2 In Fe 3 O 4 The surface of the core body self-assembles to form TiO 2The coating layer is formed to form a magnetic composite. The above method has the advantages of low synthesis temperature, short reaction time and uniform particle size of the prepared magnetic composite.
[0064] Specifically, the Fe 3 O 4 The dispersion was added dropwise to the TiO 2 dispersion, or the TiO 2 The dispersion was added dropwise to the Fe 3 O 4 In dispersion.
[0065] In some embodiments, the Fe 3 O 4 Dispersion and the TiO 2 Dispersions are all in the form of colloids.
[0066] In some embodiments, the "Fe 3 O 4 In the "dispersion preparation" operation, a water bath is used to heat the iron salt solution to a temperature of 40-60°C, and ammonia water is added dropwise under stirring at 200-500 rpm. The ammonia water is added dropwise at a speed of first rapid addition and then slow addition. The pH value of the solution is adjusted to 11, and the reaction is carried out for 1-4 hours and then aged for 2-8 hours. The obtained product is washed, centrifuged, separated, and dispersed for multiple times to obtain Fe 3 O 4 Dispersion.
[0067] In some embodiments, the iron salt solution has an iron ion concentration of 0.5 to 3 mol / L, wherein the molar ratio of divalent iron ions to trivalent iron ions is 1:2; 2 The weight of the dispersion solution is 100%, TiO 2 The added mass is 10wt.%~20wt.%.
[0068] Specifically, the divalent iron ions are derived from ferrous chloride (FeCl 2 ·4H 2 O), the trivalent iron ions are derived from ferric chloride (FeCl 3 6H 2 O), the solvent of the iron salt solution is deionized water, ferrous chloride and ferric chloride are added to the deionized water at the same time, and the ferrous chloride and ferric chloride are completely dissolved by stirring.
[0069] In other embodiments, the divalent iron ions and the trivalent iron ions may also be derived from other iron salts, such as ferrous sulfate and ferric sulfate.
[0070] Since the intermediate product Fe 3 O 4It contains both divalent iron and ferric iron, and the ratio of divalent iron to ferric iron is 1:2. Therefore, controlling the molar ratio of divalent iron ions to ferric iron ions to 1:2 can effectively ensure the Fe 3 O 4 purity to avoid the generation of Fe 3 O 4 Contains non-magnetic substances such as ferrous oxide and ferric oxide.
[0071] In some embodiments, during the “coating” operation, TiO 2 Heat the dispersion solution to 40-60°C and add Fe 3 O 4 The dispersion was added dropwise to the TiO 2 After the addition is completed, the dispersion solution is stirred at 200-400 rpm for 1-4 hours.
[0072] In some embodiments, after obtaining the magnetic composite, the magnetic composite is washed with deionized water and anhydrous ethanol, dried and then ground. The particle size of the magnetic composite after grinding is 20 to 120 nm.
[0073] Specifically, a centrifuge is used for solid-liquid separation to obtain a magnetic composite, the centrifugal speed is 2500-4500rpm, the centrifugal time is 10-60min, the separated magnetic composite is washed at a stirring rate of 150-500rpm, the washing liquid is deionized water and anhydrous ethanol, the temperature is 10-30°C, filtered and separated, the filtrate is washed with deionized water at a ratio of 1:5-50, the washing time is 5-20min, and the washing is performed 2-5 times. The washing operation can effectively remove ionic impurities on the magnetic composite, thereby avoiding the influence of ionic impurities on the subsequent preparation of lithium adsorption layer.
[0074] The washed magnetic composite is placed in a vacuum drying oven for drying at a temperature of 60 to 90° C. for 5 to 12 hours. After drying, it is ground in an agate crucible for 1 to 3 hours to obtain a magnetic composite, wherein the average particle size of the prepared magnetic composite is 30 to 80 nm and the saturation magnetization is 20 to 60 emu / g.
[0075] In some embodiments, in the "preparation of a magnetic titanium-based lithium adsorbent precursor" operation, the magnetic composite is added to a stirred titanium salt solution at a stirring rate of 300 to 500 rpm, and then a lithium salt solution is added to react, and the molar ratio of the Fe element in the magnetic composite to the Li element in the lithium salt solution is controlled to be 1:5 to 1:10, and the molar ratio of the Li element in the lithium salt solution to the Ti element in the titanium salt solution is controlled to be 0.5:1 to 1:3.
[0076] The titanium salt solution is selected from titanium salts that can react and precipitate with lithium ions.
[0077] In a preferred embodiment, in the operation of "preparing a magnetic titanium-based lithium adsorbent precursor", the titanium salt solution includes a solution of one or more of titanyl sulfate or titanic acid, and the concentration of the titanium salt solution is 1 to 4 mol / L; the lithium salt solution includes a solution of one or more of lithium chloride, lithium sulfate, lithium hydroxide, lithium nitrate and lithium acetate, and the concentration of the lithium salt solution is 1 to 3 mol / L.
[0078] The dissolving temperature of the titanium salt solution is in the range of 20 to 60° C., and the stirring speed is in the range of 150 to 500 rpm.
[0079] The stirring speed of the lithium salt solution is 150-500 rpm.
[0080] In a preferred embodiment, the lithium salt solution is selected from a lithium hydroxide solution. Compared with other lithium salt solutions, when the lithium salt solution is selected from a lithium hydroxide solution, a lithium adsorption layer with a porous structure can be formed, thereby effectively increasing the lithium adsorption amount of brine.
[0081] In some embodiments, in the operation of "preparing a magnetic titanium-based lithium adsorbent precursor", the magnetic complex, titanium salt solution and lithium salt solution are mixed, stirred for 1 to 4 hours, and then allowed to stand for 5 to 20 hours at 10 to 30°C for aging, and the intermediate product particles are filtered through a vacuum filter, the vacuum negative pressure of the vacuum filter is 0.02 to 0.08 MPa, and the filtered intermediate product particles are washed at a stirring rate of 100 to 300 rpm, the washing liquid is deionized water, the temperature is 10 to 30°C, the filtrate and deionized water are washed at a ratio of 1:5 to 50, and the washing time is 5 to 20 minutes. The washing temperature and rate should not be too high, and the washing time should not be too long, so as to avoid structural damage to the intermediate product particles. After washing, the intermediate product particles are filtered through a vacuum filter, and the vacuum negative pressure of the vacuum filter is 0.02 to 0.08 MPa.
[0082] The intermediate product particles are calcined in an air atmosphere at a temperature of 350 to 550° C. for a time of 4 to 12 hours to form a lithium adsorption layer on the surface of the magnetic composite. In this embodiment, the lithium adsorption layer obtained is Li 4 Ti 5 O 12 .
[0083] In some embodiments, before calcination, a metal salt is added to the intermediate product particles for doping, and the metal salt includes one or more salts of Mg, Cr, Co, Ni, Mo, Zr, and Zn.
[0084] During the calcination process of the metal salt, the metal ions thereof will be doped into the crystal lattice of the lithium adsorption layer to replace part of the titanium, so that the structure of the obtained lithium adsorption layer is more stable.
[0085] In some embodiments, after calcination, a metal oxide is added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating. The metal oxide includes one or more oxides of Mg, Cr, Co, Ni, Mo, Zr, Ti, Zn, and Li.
[0086] In some embodiments, the "pre-desorption" operation is used to remove part of the lithium ions in the magnetic titanium-based lithium adsorbent precursor, so that the lithium adsorption layer is in a lithium-deficient state, lithium vacancies are generated, and the lithium adsorption layer has the ability to adsorb lithium. Specifically, the magnetic titanium-based lithium adsorbent precursor and the acidic solution are pre-desorbed at a solid-liquid mass ratio of 1:10 to 100, stirred at a rate of 150 to 400 rpm, the pre-desorption temperature range is 20 to 50 ° C, the pre-desorption time is 2 to 10 hours, the acidic solution is selected from one or more of sulfuric acid solution, hydrochloric acid solution and nitric acid solution, and the acid concentration of the acidic solution is 0.5 to 2 mol / L. In this embodiment, the lithium adsorption layer Li is obtained after pre-desorption. 4-x Ti 5 O 12 .
[0087] The present invention is further described below by way of examples.
[0088] Example 1
[0089] This example is used to illustrate the magnetic titanium-based lithium adsorbent and its preparation method disclosed in the present invention, and includes the following steps:
[0090] At room temperature, ferrous chloride and ferric chloride with a molar ratio of 1:2 were prepared into an iron salt solution with a concentration of 0.5 mol / L. 2 Configuration with 10wt.% TiO 2 Colloidal solution, lithium hydroxide is prepared as lithium salt solution with a concentration of 3 mol / L, and titanyl sulfate is prepared as titanium salt solution with a concentration of 3 mol / L. Under stirring at 200 rpm, ammonia water is added dropwise to the iron salt solution at a temperature of 50°C, and the pH value of the solution is adjusted to 11. After reacting for 1 hour, aging for 4 hours, the pure Fe 3 O 4 Colloidal solution. TiO 2 The colloid, the molar ratio of titanium to iron was 1:3, stirred at 200 rpm for 2 h, separated the solid and liquid using a centrifugal dryer, washed and dried in a vacuum drying oven, and ground for 1 h to obtain a magnetic composite Fe 3 O 4 / TiO2 , slowly add it to the titanium salt solution under stirring, and then add the lithium salt solution. Make the iron-lithium molar ratio 1:5, and the lithium-titanium molar ratio 1:2. Stir for 4 hours and age for 10 hours, and filter out the intermediate product particles through a vacuum filter. After washing and filtering, put it into a muffle furnace and calcine it in an air atmosphere at a calcination temperature of 500°C for 12 hours to obtain a magnetic titanium-based lithium adsorbent precursor. At this time, the lithium adsorption layer is full of lithium Li 4 Ti 5 O 12 The magnetic titanium lithium adsorbent precursor was placed in 0.5 mol / L sulfuric acid, pre-desorbed at a solid-liquid mass ratio of 1:20, and stirred at 200 rpm for 4 hours to obtain a magnetic titanium lithium adsorbent. At this time, the lithium adsorption layer was lithium-poor Li 2.2 Ti 5 O 12 , where the magnetic core Fe 3 O 4 The particle size is 90nm, TiO 2 The layer is 10nm, Li 2.2 Ti 5 O 12 The layer is 30nm.
[0091] Example 2
[0092] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0093] The lithium salt solution is selected from lithium chloride solution with a concentration of 2 mol / L;
[0094] The titanium salt solution is selected from a metatitanic acid solution with a concentration of 2 mol / L;
[0095] The calcination temperature was increased to 400°C and the calcination time was 5 h.
[0096] Example 3
[0097] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0098] TiO 2 The concentration of the colloid was 20 wt.%.
[0099] Fe 3 O 4 Colloidal addition of TiO 2 The molar ratio of titanium to iron is 1:2, where TiO 2 The layer is 20nm.
[0100] Example 4
[0101] This example is used to illustrate the magnetic titanium-based lithium adsorbent and its preparation method disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0102] TiO 2 The concentration of the colloid was 5 wt.%.
[0103] Fe 3 O 4 Colloidal addition of TiO 2 The molar ratio of titanium to iron is 1:6, of which TiO 2 The layer is 2nm.
[0104] Example 5
[0105] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0106] TiO 2 The concentration of the colloid was 20 wt.%.
[0107] Fe 3 O 4 Colloidal addition of TiO 2 Colloid, titanium and iron element molar ratio is 1:1, of which TiO 2 The layer is 30nm.
[0108] Example 6
[0109] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0110] Lithium hydroxide was prepared into a lithium salt solution with a concentration of 0.5 mol / L, and titanyl sulfate was prepared into a titanium salt solution with a concentration of 0.5 mol / L.
[0111] Among them, the generated Li 2.2 Ti 5 O 12 The layer is 8nm.
[0112] Example 7
[0113] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0114] Lithium hydroxide was prepared into a lithium salt solution with a concentration of 0.1 mol / L, and titanyl sulfate was prepared into a titanium salt solution with a concentration of 0.1 mol / L.
[0115] Among them, the generated Li 2.2 Ti 5 O 12 The layer is 3nm.
[0116] Example 8
[0117] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0118] Lithium hydroxide was prepared into a lithium salt solution with a concentration of 6 mol / L, and titanyl sulfate was prepared into a titanium salt solution with a concentration of 6 mol / L.
[0119] Among them, the generated Li 2.2 Ti 5 O 12 The layer is 60nm.
[0120] Example 9
[0121] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0122] Before calcination, Mg(NO 3 ) 2 The lithium adsorption layer of the magnetic titanium-based lithium adsorbent is Li 2.2 Ti 4.9 Mg 0.1 O 12 .
[0123] Example 10
[0124] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0125] Before calcination, CoCO is added to the intermediate product particles. 3 The lithium adsorption layer of the magnetic titanium-based lithium adsorbent is Li 2.2 Ti 4.9 Co 0.1 O 12 .
[0126] Embodiment 11
[0127] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0128] Before calcination, Zn(NO 3 ) 2 The lithium adsorption layer of the magnetic titanium-based lithium adsorbent is Li 2.2 Ti 4.9 Zn 0.1 O 12 .
[0129] Example 12
[0130] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0131] After calcination, ZnO was added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating. The thickness of the outermost ZnO coating layer was 5 nm.
[0132] Embodiment 13
[0133] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0134] After calcination, ZnO was added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating. The thickness of the outermost ZnO coating layer was 0.3 nm.
[0135] Embodiment 14
[0136] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0137] After calcination, ZnO was added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating. The thickness of the outermost ZnO coating layer was 15 nm.
[0138] Embodiment 15
[0139] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0140] After calcination, MgO was added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating. The thickness of the outermost MgO coating layer was 5 nm.
[0141] Example 16
[0142] This example is used to illustrate the magnetic titanium-based lithium adsorbent and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that:
[0143] After calcination, Li 2 O is calcined and coated again. The outermost layer Li 2 The thickness of the O coating layer is 5 nm.
[0144] Comparative Example 1
[0145] This comparative example provides a magnetic manganese-based adsorbent and a preparation method thereof, comprising the following steps:
[0146] Fe 3 O 4 A mixed solution of ethanol and water was added, wherein the volume ratio of ethanol to water was 1:1. Tetraethyl orthosilicate was added under stirring, and the molar ratio of silicon to iron was 1:3. After stirring for 5 hours, solid-liquid separation was performed to obtain Fe 3 O 4 / SiO 2 Complex. 3 O 4 / SiO 2 The complex is added with a 2 mol / L manganese chloride solution under stirring at 500 rpm, and then a 3 mol / L lithium hydroxide solution is added with an iron:manganese molar ratio of 1:2 and a lithium:manganese molar ratio of 5:1. After stirring for 1 hour, it is allowed to stand for 12 hours to obtain a magnetic lithium manganese compound. After separation and drying, it is placed in a muffle furnace and calcined at 350°C for 5 hours to obtain a magnetic manganese-based lithium adsorbent precursor. It is added to 0.5 mol / L sulfuric acid and stirred for 5 hours to obtain a magnetic manganese dioxide lithium ion sieve.
[0147] Comparative Example 2
[0148] This comparative example provides a magnetic titanium-based lithium adsorbent and a preparation method thereof, which includes most of the operating steps in Example 1, except that:
[0149] The preparation method of the magnetic composite is as follows: Fe 3 O 4 A mixed solution of ethanol and water was added, wherein the volume ratio of ethanol to water was 1:1. Tetraethyl orthosilicate was added under stirring, and the molar ratio of silicon to iron was 1:3. After stirring for 5 hours, solid-liquid separation was performed to obtain Fe 3 O 4 / SiO 2 Complex.
[0150] Fe 3 O 4 / SiO 2 The composite replaces the magnetic composite Fe in Example 1 3 O 4 / TiO 2 Perform follow-up operations.
[0151] Performance Testing
[0152] The following performance tests were performed on the magnetic titanium lithium adsorbent and the magnetic manganese adsorbent prepared above:
[0153] Adsorption performance test:
[0154] The adsorption performance of the magnetic adsorbent was tested by taking lithium-containing brine with a pH of 12. + The concentration is 1g / L, Na + The concentration is 30g / L. Weigh 10g of magnetic adsorbent and adsorb it at a solid-liquid mass ratio of 1:30 at room temperature. The stirring rate is 300rpm and the adsorption time is 120min. After adsorption, filter it and desorb it with 0.1mol / L sulfuric acid at a solid-liquid mass ratio of 1:10. The stirring rate is 300rpm and the desorption time is 30min. The adsorbed Li + Concentration, Li + Adsorption capacity, desorption liquid Li + The concentration, Ti / Mn dissolution loss and saturation magnetization of the adsorbent are filled in Table 1. After repeating the above operation for 50 cycles, Li + Fill in the adsorption capacity in Table 1
[0155] Table 1
[0156]
[0157] It can be seen from the test results of Examples 1 to 16 and Comparative Example 1 in Table 1 that when the lithium adsorption operation is carried out in strongly alkaline brine, the magnetic titanium-based lithium adsorbent prepared by the preparation method provided by the present invention has an adsorption capacity significantly improved after lithium adsorption and desorption compared with the existing magnetic manganese-based adsorbent, and the dissolution loss of Ti is lower, while the dissolution loss of Mn of the magnetic manganese-based adsorbent reaches 64.5%, and the brine turns pink after adsorption, and a large amount of Mn is dissolved.
[0158] By comparing the test results of Examples 1 and 2, it can be seen that the selection of lithium salt and titanium salt also has a certain influence on the adsorption and analytical performance and porosity of the magnetic titanium-based lithium adsorbent. When the lithium salt is selected from lithium hydroxide and the titanium salt is selected from titanyl sulfate, it is beneficial to the formation of the porous structure of the lithium adsorption layer, thereby improving the lithium adsorption capacity.
[0159] From the test results of Examples 1, 3 to 5, it can be seen that the TiO 2 The thickness of the layer has a certain influence on the bonding strength of the lithium adsorption layer and the saturation magnetization intensity of the magnetic composite. 2When the thickness of the layer is 5 to 20 nm, the effective combination of the lithium adsorption layer and the magnetic composite can be further ensured, while avoiding the influence on the saturation magnetization intensity, which is beneficial to the magnetic separation recovery operation.
[0160] From the test results of Examples 1, 6 to 8, it can be seen that when Li 4-x Ti 5 O 12 The layer is in the range of 5 to 50 nm in thickness and has a good lithium adsorption capacity. At the same time, the magnetic titanium-based lithium adsorbent maintains a good saturation magnetization intensity.
[0161] By comparing the test results of Examples 1, 9 to 16, it can be seen that by doping with metal salts or coating with metal oxides, the adsorption performance of the magnetic titanium-based lithium adsorbent can be maintained to a certain extent and the dissolution loss of titanium can be reduced. Among them, from the test results of Examples 12 to 14, it can be seen that when the thickness of the outer coating layer is within 1 to 10 nm, the magnetic titanium-based lithium adsorbent can be completely coated and is conducive to the insertion and extraction of lithium ions.
[0162] Comparing the test results of Example 1 and Comparative Example 2, it can be seen that the TiO 2 It can improve the bonding strength between the magnetic composite and the lithium adsorption layer, thus facilitating the maintenance of Li after multiple cycles. + Stability of adsorption performance.
[0163] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A magnetic titanium-based lithium adsorbent, characterized in that: It comprises a magnetic composite and a lithium adsorption layer, wherein the lithium adsorption layer is located on the outer surface of the magnetic composite, and the lithium adsorption layer comprises lithium titanium oxide; the magnetic composite comprises a ferromagnetic magnetic core and a titanium oxide coating layer, and the titanium oxide coating layer is coated on the outer surface of the ferromagnetic magnetic core; The ferromagnetic core is selected from ferroferric oxide, the titanium oxide coating layer is selected from TiO2, and the molar ratio of the Ti element in the TiO2 to the Fe element in the ferroferric oxide is 1:2-1:5; The average particle size of the magnetic composite is 20-120 nm, the average particle size of the ferromagnetic core is 10-100 nm, the thickness of the titanium oxide coating layer is 5-20 nm, and the thickness of the lithium adsorption layer is 5-50 nm.
2. The magnetic titanium-based lithium adsorbent according to claim 1, characterized in that: The saturation magnetization intensity of the magnetic composite is 20-60 emu / g.
3. The magnetic titanium-based lithium adsorbent according to claim 1, characterized in that: The lithium adsorption layer is a porous structure, and the pore volume of the lithium adsorption layer is 0.01 ml / g to 0.30 ml / g.
4. The magnetic titanium-based lithium adsorbent according to claim 1, characterized in that: The lithium titanium oxide is selected from Li 4- x Ti 5-y M y O 12 , wherein x is selected from 0 to 2, y is selected from 0 to 0.1, and M is one or more of Mg, Cr, Co, Ni, Mo, Zr, and Zn.
5. The magnetic titanium-based lithium adsorbent according to claim 1, characterized in that: The magnetic titanium-based lithium adsorbent also includes an outer coating layer, which is located on the outer surface of the lithium adsorption layer. The outer coating layer is a metal oxide, wherein the metal oxide is one or more oxides of Mg, Cr, Co, Ni, Mo, Zr, Ti, Zn, and Li, and the thickness of the outer coating layer is 1 to 10 nm.
6. The method for preparing a magnetic titanium-based lithium adsorbent according to any one of claims 1 to 5, characterized in that: The steps include: Obtaining a magnetic composite: the magnetic composite comprises a ferromagnetic core and a titanium oxide coating layer; Preparation of magnetic titanium-based lithium adsorbent precursor: adding the magnetic complex to a titanium salt solution and a lithium salt solution for reaction, and separating to obtain intermediate product particles; calcining the intermediate product particles to form a lithium adsorption layer on the outer surface of the magnetic composite to obtain a magnetic titanium-based lithium adsorbent precursor; Pre-desorption: The magnetic titanium-based lithium adsorbent precursor is placed in an acidic solution for pre-desorption treatment to remove part of the lithium in the lithium adsorption layer to obtain the magnetic titanium-based lithium adsorbent.
7. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 6, characterized in that: The preparation method of the magnetic composite comprises the following steps: Preparing an iron salt solution: the iron salt solution includes divalent iron ions and trivalent iron ions; Preparation of Fe3O4 dispersion: Add ammonia water to the iron salt solution at a temperature of 40-60°C to separate the Fe3O4 dispersion; Coating: Nano-TiO2 is configured to obtain a TiO2 dispersion, Fe3O4 dispersion and TiO2 dispersion are mixed, and solid-liquid separation is performed to obtain a magnetic composite.
8. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 7, characterized in that: In the iron salt solution, the iron ion concentration is 0.5~3 mol / L, wherein the molar ratio of divalent iron ions to trivalent iron ions is 1:2; based on the weight of the TiO2 dispersion solution as 100%, the added mass of TiO2 is 10 wt.%~20 wt.%.
9. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 7, characterized in that: After obtaining the magnetic composite, the magnetic composite is washed with deionized water and anhydrous ethanol, dried and then ground. The particle size of the magnetic composite after grinding is 20-120 nm.
10. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 6, characterized in that: In the "preparation of a magnetic titanium-based lithium adsorbent precursor" operation, the magnetic composite is added to a stirred titanium salt solution, and then a lithium salt solution is added for reaction, and the molar ratio of the Fe element in the magnetic composite to the Li element in the lithium salt solution is controlled to be 1:5-1:10, and the molar ratio of the Li element in the lithium salt solution to the Ti element in the titanium salt solution is controlled to be 0.5:1-1:
3.
11. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 6, characterized in that: In the "preparation of a magnetic titanium-based lithium adsorbent precursor" operation, the titanium salt solution includes a solution of one or more of titanyl sulfate or metatitanic acid, and the concentration of the titanium salt solution is 1 to 4 mol / L; the lithium salt solution includes a solution of one or more of lithium chloride, lithium sulfate, lithium hydroxide, lithium nitrate and lithium acetate, and the concentration of the lithium salt solution is 1 to 3 mol / L.
12. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 6, characterized in that: Before calcination, metal salts are added to the intermediate product particles for doping.
13. The method for preparing a magnetic titanium-based lithium adsorbent according to claim 6, characterized in that: After calcination, metal oxide is added to the magnetic titanium-based lithium adsorbent precursor and calcined again for coating.
Citation Information
Patent Citations
Magnetic separable metatitanic acid lithium ion sieve, preparation method and application of lithium ion sieve
CN108212074A
Magnetic aluminium-based lithium adsorbent and preparation method thereof
CN109012567A